Mobilitas Berkelanjutan: Meningkatkan Minat Pembelian Ulang Melalui Kualitas Layanan Dan Promosi Yang Ditargetkan Pada Industri Bus - Al-Aulawi, Abdurrahman; Roosdhani, Mohammad Rifqy (Universitas Batanghari Jambi, 2023)
In this modern era, the industrial and business sectors are experiencing rapid development, including in the mass transportation services industry such as buses. This encourages business owners to compete in a very tight competitive environment. The approach used is quantitative with 100 samples, which are analyzed by the SEM method using the Smart-PLS version 4.0 tool. The testing used outer model testing, inner model testing, mediation testing, and hypothesis testing. The results of the validity test indicate that the loading factor value > 0.7 and the AVE value > 0.5 are valid. In the reliability test, the composite reliability value and Cronbach's alpha value > 0.7 are considered reliable. It can be concluded that service quality and promotion have a positive and significant influence on repurchase intention. Mediation testing shows that the quality of service variable on repurchase intention is mediated by purchase decision, which is stated as Partial mediation. The promotion variable on repurchase intention is mediated by purchase decision, which is stated as Partial mediation.